Mitigation of data breaches for online customers in South Africa - Shepperson, Michael Saunders (My University, 2018)
Technological advances and increasing access to the internet has allowed customers from all over the world to access online shopping platforms. This has contributed significantly to the growth of the customer base of online shopping companies. Cybercrime has emerged as the biggest threat to the online shopping industry. All online shopping companies face the risk of a cyber-attack, generally through a data breach. These data breaches compromise the personal and financial details of the customer base, exposing customers to a further broad range of cybercrimes. Many online shopping companies believe they will not be exposed to a data breach and rely heavily on outdated cybersecurity infrastructure and procedures. Furthermore, these companies do not have a comprehensive Data Breach Response Plan to utilise in the event of a data breach. However, in the event of a data breach, many companies just do not know how to retain their customer base. Data collected quantitatively from respondents who shop online, via an electronic survey, examines what methods and attributes an online shopping company could use or offer to its affected customer base to retain their patronage. Data breaches negatively impact the trust a customer has in the online shopping company. It is this trust initially that convinces a customer to utilise the services of the online shopping company. Online shopping companies need to offer a wide range of attributes to retain some of their customer base. However, despite providing customers with every conceivable option, there is a strong possibility that an online shopping company will only be able to retain roughly half the customers that were affected by the data breach. Online shopping companies need to establish and maintain a comprehensive cybersecurity policy and ensure that their staff are fully trained. Overall, online shopping companies need to develop more comprehensive cybersecurity policies to help militate against the threat of data breaches, as a data breach can efficiently extinguish customer trust, which online shopping companies need to conduct business
A research article submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in partial fulfillment of the requirements for the degree of Master of Business Administration Johannesburg, 2018